Smart membrane materials and systems from flat membranes to microcapsule membranes - Chu, Liang-Yin; SpringerLink (Online service). (Hangzhou Zhejiang University Press ; Berlin : Springer, 2011)
Smart Membrane Materials and Systems: From Flat Membranes to Microcapsule Membranes comprehensively and systematically treats modern understanding of smart or intelligent membranes with environmental stimuli-responsive functions. The contents range from flat membranes to microcapsule membranes with various response properties, such as thermo-response, pH-response, glucose-response, molecular-recognition, and dual-/multi-stimuli-response. While chapters may be read as stand-alone, together they clearly describe cover design concepts, fabrication strategies and methods, microstructures and performances of smart membranes. Vivid schematics and illustrations throughout the book enhance accessibility to the theory and technologies. The book is intended for researchers and postgraduate students in membrane science and technology, separations and controlled-release.  Dr. Liang-Yin Chu is a professor at the School of Chemical Engineering, Sichuan University, China. He is a Distinguished Young Scholar of the National Natural Science Foundation of China and a Distinguished Professor of Chang Jiang Scholars Program of the Ministry of Education of China.
Introduction -- Thermo-Responsive Gating Membranes: Design, Microstructures and Performances -- Smart Microcapsules with Thermo-Responsive Gating Membranes -- Smart Microcapsules with Thermo-Responsive Hydrogel Membranes -- Thermo-Responsive Membranes for Chiral Resolution -- Thermo-Responsive Membranes for Affinity Separation -- pH-Responsive Gating Membrane Systems with Pumping Effects -- Smart Microcapsules with pH-Responsive Hydrogel Membranes -- Glucose-Responsive Gating Membranes -- Molecular-Recognizable Smart Membranes -- Dual-/Multi-Stimuli-Responsive Smart Membranes -- Perspectives of Smart Membrane Materials and Systems.
Electronic reproduction.
Keywords: Biomimetic materials; Smart materials